Biomechanical and physiological differences between males and females during freestyle swimming - Dutto, D. J.; Cappaert, J. M. (Medicine & Science in Sports & Exercise, 1994)
The purpose of this study was to compare morphological, biomechanical, strength/power, and physiological characteristics between male and female age group swimmers. For biomechanical data analysis, video records were taken at 1.35 m . s(-1). Subjects performed a swimming economy test consisting of four submaximal swims and one maximal effort to determine 02 uptake. Anthropometric measurements were taken on all participants. Strength and power were measured using a standard protocol of decreasing resistance on a biokinetic swimbench. Despite segment length differences, females pulled deeper (left arm: 1.0±0.1m to 0.9± 1m for males) and narrower than males (left arm: 0.2±0.1m to 0.3±0.1m for males). Females were found to have lower propulsive forces during the insweep and finish phases of the stroke (right arm, finish: females = 16.9±2.9 N, males = 31.8±14.7 N, p<0.5). Power was greater for males than for females at all four settings (p<0.05), but when the values were expressed relative to lean body weight the differences were no longer significant at swimming specific speeds. Females had lower slopes in their economy regression lines (a=0.4±0.2 for females and a+0.7±0.2 for males, p<0.05). Comparisons at 1.35 m . s(-1) showed that females consumed a lower percentage of their VO2 max (49.1±10.8% for females and 62.±1.6% for males, p>0.5). These data suggest that females may have the potential to be more efficient swimmers that males, but they lack the absolute strength and power to achieve comparable performance times.